Antifungal and antimycotoxigenic activity of allyl isothiocyanate on barley under different storage conditions. (September 2019) - Nazareth, Tiago de Melo; Quiles, Juan Manuel; Torrijos, Raquel; Luciano, Fernando Bittencourt; Mañes, Jordi; Meca, Giuseppe
Abstract: The present study evaluated the efficacy of allyl isothiocyanate (AITC) in avoiding the growth of Penicillium verrucosum and consequent ochratoxin A (OTA) production in barley during storage for 90 d. Environmental humidity was controlled using saturated salt solutions and moisture content (MC) of the grain was analyzed. Moreover, the residual concentration of AITC on stored barley was also examined. Samples with 20.6% of MC presented the highest absorption of AITC with levels ranging from 75 to 4 mg/kg at day 1 and 90, respectively. The population of P. verrucosum was significantly reduced after 24 h of AITC exposure. After 90 d, the non-treated control group reached a fungal population of 8.3 log CFU/g and 1.5 mg/kg of OTA. On the other hand, AITC at 50 μL/L was able to reduce the fungal population as well as the production of OTA to levels that were below the limit of detection, independently of the MC and the time of exposure. In conclusion, the AITC was absorbed by the barley and released gradually, inhibiting the growth of P. verrucosum and the production of mycotoxin. Therefore, AITC could be used as a fungicide to prolong the shelf life of the barley improving its safety. Highlights: AITC avoid the Penicillium verrucosum growth in barley stored for 90 days. Fumigation of AITC could be used to improve barley safety. 50 μL/L of AITC avoid Ochratoxin A production regardless of grain moisture content.